Earth observation (EO) applications in pastoral systems - Fava, Francesco P.; Ceriani, Rodolfo; Saavedra, Natalia; Colombo, Marta; Marinis, Pietro de; Bocci, Stefano (University of Milan, 2025)
Presented at the Jameel Observatory drylands food security and resilience early action research and evidence dialogue, Addis Ababa, Ethiopia, 15-16 May 2025